The communication and dissemination of information about HIV/AIDS awareness and prevention in the South African mining industry, with reference to Kumba Iron Ore - Thompson, J.E. (Lisa) (University of Pretoria, 2013)
Dissertation (MIT)--University of Pretoria, 2012.